Pengembangan Awal Alat Pemanen Alga Sistem Rotating Filtered-Drum Untuk Perbaikan Kualitas Air di Perairan Tergenang - Bahri, Syamsul; Arisanto, Pranu; Suhardi, Suhardi; Herwindo, Wildan (Jurnal Inovasi Konstruksi, 2023)
The phenomenon of overgrowth of green algae and cyanobacteria indicates a serious aquatic environmental problem from eutrophication. In aquatic ecosystems, algae are an integral part of the ecological system. But when there is abundant algae growth in the waters it causes the phenomenon of harmful alga blooms. Algae that were previously invisible, due to clumping, this group becomes invisible to the eye. The follow-up impact of the algae blooms is fish death, due to lack of oxygen at night. Algal masses that are swept by the wind onto the shores of bays and reservoir shores cause buildup and decay. Among the efforts that can be made in dealing with the phenomenon of abundant algae in waters is harvesting. In this study, the technique of harvesting by filtration and centrifugal rotation in a drum was applied. The purpose of this study was to design and build a filtration system algae harvester with a Rotating Filtered-Drum type. The results of preliminary research on filtration of water contaminated with algae from the facultative pond of the Bojongsoang-Bandung WWTP by gravity showed that the T 165 filter was able to reduce TSS levels as an indicator of algae by 72.85%. The Rotating Filtered-Drum tool requires further research for operational trials using pool water contaminated with algae. Keywords: algal blooming, lentic waters, euthrophic, green algae, cyanobacteria.